Entrepreneurship and employment growth across European regions. Issue 1 (1st January 2016) - Doran, Justin; McCarthy, Noirin; O'Connor, Marie
Abstract : This research focuses on the impact of regional entrepreneurial activity on employment growth. Specifically it analyses whether new firm formation in European NUTS-2 regions can stimulate job creation and drive employment growth.